2016
DOI: 10.1002/adsc.201501088
|View full text |Cite
|
Sign up to set email alerts
|

Tin‐Catalyzed Selective Reductive Hydroamination of Alkynes for the Synthesis of Tertiary Amines

Abstract: Au niquep reference of tin(II) for aniline activation is disclosed. In the present workt in(II) triflate-catalyzedh ighly selective Markovnikov reductive hydroaminationo fi nternala sw ell as terminal alkynes is reported. Them echanistic study revealed the involvement of twos teps in one pot wherein alkyne reducest oc orresponding alkene in presence of PMHS as reducing agent followed by hydroamina-tion of alkene.Abroad range of alkynes transformed into tertiary amines with good to excellent yield. This method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 38 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…However, the major disadvantages of these protocols involved prolonged reaction time, high catalyst loading, ligand and elevated temperature for the N ‐ alkylation of secondary amine. Nevertheless, N‐alkylation of secondary arylamines with secondary benzyl alcohols is still a challenge due to the following reasons: (a) the larger size of secondary arylamines; they are generally considered more difficult coupling partners than primary anilines for N‐arylation reactions,, (b) as an alkylating agent, secondary alcohols are less reactive substrates as compared to primary alcohols in borrowing hydrogen transfer strategy because of the difficulty in its in situ dehydrogenation to the corresponding ketones,, (c) the hydrogenation of the iminium or enamine intermediate is also challenging (Scheme b) ,,…”
Section: Introductionmentioning
confidence: 69%
“…However, the major disadvantages of these protocols involved prolonged reaction time, high catalyst loading, ligand and elevated temperature for the N ‐ alkylation of secondary amine. Nevertheless, N‐alkylation of secondary arylamines with secondary benzyl alcohols is still a challenge due to the following reasons: (a) the larger size of secondary arylamines; they are generally considered more difficult coupling partners than primary anilines for N‐arylation reactions,, (b) as an alkylating agent, secondary alcohols are less reactive substrates as compared to primary alcohols in borrowing hydrogen transfer strategy because of the difficulty in its in situ dehydrogenation to the corresponding ketones,, (c) the hydrogenation of the iminium or enamine intermediate is also challenging (Scheme b) ,,…”
Section: Introductionmentioning
confidence: 69%
“…To overcome the challenges associated to developed protocols, our group have developed new catalytic approaches for the synthesis of tertiary amines using various alkylating agents such as carbonyls and alkynes via an alternative carbocationic pathway . During our previous study on the direct reductive N‐alkylation of secondary anilines with carbonyl compounds, we found that initially, the carbonyl compound is reduced to alcohol intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…In analogy to pervious reported Sn catalyzed C−N bond forming reactions, initially, the alcohol undergoes silylation in the presence of tin(II) triflate and polymethylhydrosiloxane (PMHS). Concurrently, the aniline interacts with Sn(OTf) 2 to generate tin(II) amidinium complex ( A ) . Further, this complex A protonates B to form the benzylic cation ( D ) via desilylation of intermediate C .…”
Section: Introductionmentioning
confidence: 99%